2002
DOI: 10.1002/1521-396x(200207)192:1<195::aid-pssa195>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

MBE Growth and Characterization of Hexagonal ZnCdSe Layers on GaAs(111)-A and -B Substrates

Abstract: Jk; 81.05.Dz; 81.15.Hi Zn 0.5 Cd 0.5 Se epilayers were grown on GaAs(111)-A and -B substrates by MBE. We investigated how the polarity of the substrate affects both the epilayer crystalline structure and quality. It was found that the epilayers consisted of hexagonal and cubic phases independent of the substrate polarity. The hexagonal phase content in the epilayers tended to be minimal at a growth temperature around 300 C; it increased with decreasing growth temperature in the range of 200-300 C and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…2 Author to whom any correspondence should be addressed. be improved by replacing the normally cubic-structured active layer with a hexagonal one [9]. ZnSe 1D structures have been studied extensively due to their significant importance in basic science and practical applications [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…2 Author to whom any correspondence should be addressed. be improved by replacing the normally cubic-structured active layer with a hexagonal one [9]. ZnSe 1D structures have been studied extensively due to their significant importance in basic science and practical applications [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…3 Results and discussion First, it was found that the hexagonal phase purity of Zn 0.5 Cd 0.5 Se epilayers was improved by inserting LT-CdS buffer layers in preliminary experiments. The maximum values of hexagonal phase purities in Zn 0.5 Cd 0.5 Se epilayers without LT-buffer were 42% for the (111)A surface and 82% for the (111)B surface [5]. While, those in Zn 0.5 Cd 0.5 Se epilayers with LT-buffer were 70% and 95% for the (111)A and B surfaces, respectively.…”
Section: Introductionmentioning
confidence: 88%
“…Until now, we have grown hexagonal ZnCdSe epilayers on GaAs(111) substrates by molecular beam epitaxy (MBE) for the green light emitting device applications, and reported that the cubic phase was incorporated into the hexagonal epilayers [5]. However, if the hexagonal phase purity of ZnCdSe epilayers can be improved, a hexagonal ZnCdSe/ZnCdMgSe quantum well (QW) structure becomes one of the suitable green LD structures.…”
Section: Introductionmentioning
confidence: 99%